Host-derived chimeric peptides clear the causative bacteria and augment host innate immunity during infection: A case study of HLB in citrus and fire blight in apple - Basu, Supratim; Sineva, Elena; Nguyen, Liza; Sikdar, Narattam; Park, Jong Won; Sinev, Mikhail; Kunta, Madhurababu; Gupta, Goutam (Frontiers in Plant Science, 2022)
Bacterial diseases cause severe losses in the production and revenue of many fruit crops, including citrus and apple. Huanglongbing (HLB) in citrus and fire blight in apple are two deadly diseases without any cure. In this article, we introduce a novel therapy for HLB and fire blight by enhancing the innate immunity of the host plants. Specifically, we constructed in silico a library of chimeras containing two different host peptides with observed or predicted antibacterial activity. Subsequently, we performed bactericidal and toxicity tests in vitro to select a few non-toxic chimeras with high antibacterial activity. Finally, we conducted ex planta studies to show that not only do the chimeras clear the causative bacteria from citrus leaves with HLB and from apple leaves with fire blight but they also augment the host’s innate immunity during infection. This platform technology can be extended to design host-derived chimeras against multiple pathogenic bacteria that cause diseases in plants and animals of agricultural importance and in humans.